What is the normal tissues morbidity following Helical Intensity Modulated Radiation Treatment for cervical cancer?. Issue 3 (June 2015) - Mouttet-Audouard, Raphaelle; Lacornerie, Thomas; Tresch, Emmanuelle; Kramar, Andrew; Le Tinier, Florence; Reynaert, Nick; Leblanc, Eric; Narducci, Fabrice; Lartigau, Eric; Nickers, Philippe
Abstract Background and purpose To report on normal tissues morbidity following IMRT for cervix cancer. Material and methods The first 61 patients of a prospective series were included. 50 Gy to the PTV 1(pelvis) and 60 Gy to the PTV 2 (centro-pelvic disease and GTV nodes) were delivered concomitantly in 28 fractions, followed by a brachytherapy boost. For the small bowel, 50 Gy was the maximal dose, while V45 and V40 had to be <50 cc and 200 cc, respectively. For the bladder, rectum and sigmoid structures, 60 Gy was the maximal dose, and V45 and V40 had to be <20% and <50%. Acute and late toxicity data were prospectively collected. Results The median follow-up period was 40 months (range: 23–60). 30% and 90% of acute and moderate late side effects were reported respectively. Considering the AUC data of the organs at risk (OAR) DVH, late morbidity and doses were significantly linked (p ⩽ 0.03), predominantly between 10 Gy and 40 Gy, considering the small bowel and sigmoid colon. The high dose regions exhibited no significant impact. Conclusion The moderate dose volumes represent the predominant cause of morbidity after IMRT. Prospective trials are thus required to investigate new ways of dose distribution within the OAR.